Plane Strain Fracture Toughness Determination for Magnesium Alloy - Mohd Daud, Mohd Ahadlin (Fakulti Kejuruteraan Mekanikal (FKM), Universiti Teknikal Malaysia Melaka (UTeM), 2012)
A stress intensity factor K was used as a fracture parameter to determine the true material property, i.e. plane strain fracture toughness K of AZ61 magnesium alloy using a single edge notch bend (SENB) specimen in accordance to ASTM E399 testing method. Five different specimen thicknesses of 2 to 10 mm were used in the test. A sharp fatigue pre-crack was initiated and propagated to half of specimen width at a constant crack propagation rate of about 1 x 10-8 m/cycle before the specimen was loaded in tension until the fracture stress is reached and then rapid fracture occurred. The fracture toughness K values obtained for different thicknesses showed that KC value decreased with increasing specimen thickness. The highest KC value obtained was 16.5 MPa√m for 2 mm thickness specimen. The value of K became relatively constant at about 13 MPa√m when the specimen thickness exceeds 8 mm. This value was then considered as the plane strain fracture toughness K of AZ61 magnesium alloy. Calculation of the minimum thickness requirement for plane strain condition and the size of the shear lips of the fracture surface validate the obtained K value.